Finite Element Analysis (FEA) of fatigue case studies - Muhammad Rohaizad (Nanyang Technological University, 2020)
This Final Year Project focuses on the crack propagation rate and fatigue lifespans of cruciform joints in the presence of weld toe and weld root crack. Weld root crack caused by partial penetration and residual stress due to welding are 2 most common defects found in cruciform joints. These defects can deteriorate the fatigue strength of the material significantly. Thus, it is critical to analyse the fatigue properties of cruciform joints to accurately predict fatigue lifespans. Inaccuracy in predicting fatigue lifespan of structures may lead to structural failure which can be catastrophic. There are various methods for fatigue assessment of welded joints however fracture mechanics concept are used for fatigue assessment in this report. In this study, Extended Finite Element Method (XFEM) simulations were performed using ABAQUS CAE software to study the fatigue properties under the given conditions. These cruciform joint models are applied under various loads. The fatigue lifespan and the crack propagation rate of the models were retrieved from the simulations results. Thereafter, these simulations results were compared with theoretical calculations. The fatigue lifespan of the cruciform joint with cracks were compared with a defect free cruciform joint to create a relation between the crack and the fatigue strength of the joint. The theoretical calculations are based on past research paper. The SN curve to predict the fatigue lifespan was plotted based on Basquin’s Equation while the crack propagation rate was calculated based on International Institute of Welding (IIW) guide.